Effect of spraying GA, IAA and BA in growth Olive seedlings Olea europaea L. forcultivars Ashresi and Nabali After individualization - Flayyih, Sabah Abd; Edian, Razak Eewyaz; Aziz, Harith Mahmoud; Mohmood, Ola H. (Journal of Kerbala for Agricultural Sciences, 2018)
This research was conducted in private orchard located at Husseiniya /Karbala province. For the period from mid- March 2016 until a mid –july2016.to study the effect of spraying growth regulators GA3 ,IAA and BA with concentrations (50,100,100,mg.l-1) sequentially in olive seedling for cultivars Ashresi and Nabali after individualization In addition to the Treatment of water- only comparison. Olive seedling were sprayed with growth regulator from 15/3/2015 to 15/7/2016 between spray and another 30 days using (RCBD) design with four replicates. Results showed that all spray treatment with growth regulator only or incombin led to a significant increase in vegetative growth characteristics the plant height , stem diameter, number of branches, length of the branch , leaf area and the percentage of dry matter. The interaction treatments is also excelled (GA3+IAA) and treatment.(GA3+BA)giving it the highest of the branch leaf area as it reached (27.37,81.56,11.51,8.22)respectively.